Wheel rut measurements by forest machine-mounted LiDAR sensors - accuracy and potential for operational applications? - Aura Salmivaara; Mikko Miettinen; Leena Finér; Samuli Launiainen; Heikki Korpunen; Sakari Tuominen; Jukka Heikkonen; Paavo Nevalainen; Matti Sirén; Jari Ala-Ilomäki; Jori Uusitalo (TAYLOR & FRANCIS INC, 2022)
Soil rutting caused by forest operations has negative economic and ecological effects and thus limits for rutting are set by forest laws and sustainability criteria. Extensive data on rut depths are necessary for post-harvest quality control and development of models that link environmental conditions to rut formation. This study explored the use of a Light Detection and Ranging (LiDAR) sensor mounted on a forest harvester and forwarder to measure rut depths in real harvesting conditions in Southern Finland. LiDAR-derived rut depths were compared to manually measured rut depths. The results showed that at 10-20 m spatial resolution, the LiDAR method can provide unbiased estimates of rut depth with root mean square error (RMSE) < 3.5 cm compared to the manual rut depth measurements. The results suggest that a LiDAR sensor mounted on a forest vehicle can in future provide a viable method for the large-scale collection of rut depth data as part of normal forestry operations.